Kebijakan Lingkungan Hidup di Indonesia dalam Perspektif Hukum Pidana - Setiawan, Tomi; Mughits, Muhammad Hammam (Universitas Medan Area, 2025)
This paper aims to explain the effectiveness of environmental policy in Indonesia through the perspective of criminal law. The environmental crisis in Indonesia continues to be a serious concern due to the rise of environmental crimes throughout 2023, there were 3,835 cases of crimes against the environment based on the Central Statistics Agency report an increase from the previous year which only amounted to 2,492 cases. One important approach in dealing with this issue is the use of criminal law as a tool to provide a deterrent effect and ensure environmental sustainability. This research uses a doctrinal legal research method. The focus of this research involved analyzing legal norms in relevant legislation, doctrine, and jurisprudence, particularly Law Number 32 of 2009 on Environmental Protection and Management. The results show that although Indonesia has a progressive legal framework, its implementation still faces obstacles that include weak law enforcement and limited capacity of law enforcement officials. Moreover, this research emphasizes the need for reform of the environmental criminal law framework that integrates the principle of strict liability in writing into legislation and the need for the establishment of regulations that have binding legal force regarding the mechanism for implementing environmental restoration in writing to ensure fair and effective recovery of environmental damage.